Effect of Education and Cardboard Bassinet Distribution on Newborn Bed-Sharing. (February 2019) - Heere, Megan; Moughan, Beth; Alfonsi, Joseph; Rodriguez, Jennifer; Aronoff, Stephen
Objective. This study sought to determine if infant sleep education plus a cardboard bassinet reduced bed-sharing, a risk factor for sudden infant death syndrome (SIDS) and sleep-related deaths (SRD), in the first week of life. Methods. Women delivered between 1/1/2015-11/15/2016 were interviewed by phone within 72 hours of discharge. Control 1 delivered through 10/31/2015 (previously reported); Control 2: 11/1/2015-2/7/2016; Intervention 1 received inpatient safe sleep education and delivered between 2/8/2016-5/4/2016; Intervention 2 also received a cardboard bassinet and delivered after 5/4/2016. Subjects self-reported bed-sharing, newborn sleep position, feeding method, and sleep environment; demographic data was obtained from medical records. Bayesian methodology compared bed-sharing rates between aggregated control and intervention groups; results were expressed as posterior rates, rate ratios, and 95% credible intervals (CredInt); the posterior probability that the rate ratio was > 1(Bayesian probability) was determined by calculation and simulation. Results. 5187 eligible subjects, 2763 (53%) completed the survey (Control 1: n=1264; Control 2: n=423; Intervention 1: n=391; Intervention 2: n=685). Bed-sharing rates: Control: 6.3% (5.2, 7.4); Intervention: 4.7% (3.5, 5.9). Rate ratio (Control/Intervention) was 1.36 (0.95, 1.83) and the Bayesian probability that the rate ratio >1 was .96 and .97 by calculation and simulation, respectively. Bed-sharing rates for exclusively breastfed infants: Control: 11% (7.4, 14.6); Intervention: 5.9% (2.7, 9.2); Rate ratio was 2.00 (1.01, 3.15) and the Bayesian probability that the rate ratio >1 was .993. Conclusions. Infant sleep education plus a cardboard bassinet reduced the rate of bed-sharing in the first week of life, particularly among exclusively breastfeeding dyads.